Influence of adhesive systems on microtensile bond strength of resin-based endodontic sealers to the root dentin - Rodríguez-Martínez, Juan B. (Medicina Oral S.L., 2014)
Objective: The aim of this study was to determine the microtensile bond strength to root dentin of AH Plus™ and EndoREZ® with Clearfil Liner Bond 2V and Optibond Solo™ Plus adhesive systems. Study Design: The coronal and middle thirds of six single rooted bovine teeth was split longitudinally in a mesio-distal direction. The two halves were joined with AH Plus or EndoREZ, with and without the use of Clearfil Liner Bond 2V and Optibond Solo™ Plus adhesive systems. Build-ups were vertically sectioned into quadrangular (≈1mmx1mm) compound bars and subjected to tensile tests at a constant crosshead speed (1 mm/min) until debonding. Results: Optibond® Solo Plus™ in combination with AH Plus™ and EndoREZ® showed the highest mean microtensile bond strength values, in both coronal and middle thirds. The lowest results were seen in the groups where no dentine adhesive was applied, and in those where the self-etching adhesive Clearfil Liner Bond 2V was used. Conclusion: The microtensile bond strength to root dentin of AH Plus™ and EndoREZ may be increased with the use of a total-etch adhesive. Key words:Adhesive systems, AH Plus, EndoREZ, microtensile bond strength, root dentin.